γ-PS-generalized closed sets and γ-PS-T 1/2 spaces - Asaad, Baravan A.; Ahmad, Nazihah; Omar, Zurni (Academic Publications, Ltd., 2014)
This paper defines new class of sets called γ-PS-generalized closed using γ-PS-open set and τγ-PS-closure of a set in a topological space.By using this new set, we introduce a new space called γ-PS-T 1/2 and define three functions namely γ-PS-g-continuous, γ-PS-g-closed and γ-PS-g-open.Some theoretical results and properties for this space and these functions are obtained. Several examples are given to illustrate some of the results.